Welfare Effects of Intellectual Property in a North-South Model of Endogenous Growth with Comparative Advantage - Gilles Saint-Paul (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
This paper develops a model for analyzing the costs and benefits of intellectual property enforcement in LDCs. The North is more productive than the South and is the only source of innovator. There are two types of goods, and each bloc has a comparative advantage in producing a specific type of good. If comparative advantage is strong enough, even under piracy there are goods that the South will not produce. Piracy will then lead to a reallocation of innovative activity in favor of these goods. That may harm consumers (including consumers in the South) to the extent that these goods have smaller dynamic learning externalities than the other goods, and that their share in consumption is small. Thus, whether or not piracy is in the interest of the South depends on how important are the goods for which it has a comparative advantage to its consumers, and what the growth potential of these goods is. While, all else equal, the North tends to lose more (or gain less) from piracy than the South, because monopoly profits eventually accrue to the North, the South may lose more than the North if there is a strong enough home bias in favor of the goods for which it has a comparative advantage.
Keywords: O34; O30; F13; F12; 330; Piracy; intellectual property; innovation; growth; comparative advantage; Nord-Süd-Beziehungen; Immaterialgüterrechte; Produktpiraterie; Neue Wachstumstheorie; Komparativer Kostenvorteil; Entwicklungsländer